Using and not using the past after the Carolingian Empire, c. 900-c.1050
1 online resource
Keywords: "Using and Not Using the Past after the Carolingian Empire offers a new take on European history from c.900 to c.1050, examining the 'post-Carolingian' period in its own right and presenting it as a time of creative experimentation with new forms of authority and legitimacy"--